2021
DOI: 10.3389/fvets.2020.604628
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Pharmacokinetics of Four Long-Acting Injectable Formulations of Enrofloxacin in Pigs

Abstract: A comparative study on pharmacokinetics of four long-acting enrofloxacin injectable formulations was investigated in 36 healthy pigs after intramuscular injection according to the recommended single dose @ 2.5 mg/kg body weight. The drug concentrations in the plasma were computed using high-performance liquid chromatography (HPLC) with fluorescence detection. WinNonLin5.2.1 software was used to analyze the experimental data and compared it under one-way ANOVA using SPSS software with a 95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Co-resistance against multiple drug classes makes the problem of AMR in bacteria even more complex, as use of one class of antimicrobials can provide positive selection pressure to maintain resistance against other antimicrobial classes ( Holmes et al, 2016 ). Fluoroquinolones are also considered as critically important antimicrobials in human medicine ( World Health Organization., 2019 ) and are also used in food animals in some countries for treatment purposes ( Römer et al, 2017 ; Ahmad et al, 2021 ). Co-resistance to fluoroquinolones and 3GCs can hence be considered both a human and animal health threat.…”
Section: Discussionmentioning
confidence: 99%
“…Co-resistance against multiple drug classes makes the problem of AMR in bacteria even more complex, as use of one class of antimicrobials can provide positive selection pressure to maintain resistance against other antimicrobial classes ( Holmes et al, 2016 ). Fluoroquinolones are also considered as critically important antimicrobials in human medicine ( World Health Organization., 2019 ) and are also used in food animals in some countries for treatment purposes ( Römer et al, 2017 ; Ahmad et al, 2021 ). Co-resistance to fluoroquinolones and 3GCs can hence be considered both a human and animal health threat.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of animal species, when it is necessary to use the prescribing cascade principle, extrapolation from human doses is used due to the lack of knowledge of the pharmacokinetic parameters and, therefore, the most appropriate dosing regimens, which may cause problems in treated animals. In this context, in veterinary medicine, the special conditions for the treatment of animals make long-acting formulations powerful tools for use in animals affected by diabetes (and other medical conditions) [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…59 The conversion of enrofloxacin to ciprofloxacin varies in different species of mammal from 59% in dairy cows to 51.5% in pigs. 60 This rate of conversion has important implications for determining the appropriate dose to administer to achieve the desired antimicrobial effect from this therapeutic. For the pharmacokinetics of enrofloxacin in birds, chickens have been studied extensively and a comprehensive population analysis by Guo et al report that after IV administration 30% of enrofloxacin was metabolized to ciprofloxacin in chickens.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In a study in dogs, it was found that 40.44 ± 10.08% of an enrofloxacin-administered IV was metabolized to ciprofloxacin and a similar conversion was found following oral administration (40.17 ± 8.33%) . The conversion of enrofloxacin to ciprofloxacin varies in different species of mammal from 59% in dairy cows to 51.5% in pigs . This rate of conversion has important implications for determining the appropriate dose to administer to achieve the desired antimicrobial effect from this therapeutic.…”
Section: Discussionmentioning
confidence: 99%